PVP influence on Mn–CdS for efficient photocatalytic activity. (August 2021) - Keerthana, SP.; Yuvakkumar, R.; Ravi, G.; Mustafa, Abd El-Zaher M.A.; Al-Ghamdi, Abdullah Ahmed; Soliman Elshikh, Mohamed; Velauthapillai, Dhayalan
Abstract: Wastewater treatment is the most serious problem in this upcoming era. A harmful effluent like organic dyes, heavy metals, acids from industries mixed in wastewater is deteriorating the environment. To get rid of these poisonous materials and to recycle wastewater for domestic purposes, there are many steps which included photocatalytic dye degradation. PVP assisted Mn–CdS nanoparticles was prepared by novel hydrothermal technique. The characteristic behavior of pure and PVP (1% and 2%) assisted Mn–CdS samples were studied by further analysis. The structural, optical, vibrational, morphological, chemical composition behavior of synthesized pristine and surfactant induced Mn–CdS nanoparticles were analyzed. UV–Vis spectra revealed the optical behavior of the prepared pure and PVP (1% and 2%) assisted Mn–CdS samples. The bandgap obtained was 2.2, 2.06 and 1.99 eV for pure Mn–CdS, 1% PVP-Mn-CdS and 2% PVP- Mn-CdS. The narrow bandgap is one of the advantage of the material. Mn–CdS, 1% PVP-(Mn–CdS) and 2% PVP- (Mn–CdS) morphology were further investigated by Scanning Electron Microscopic studies (SEM). The surfactant (PVP) was added to enhance the morphology development and decrease agglomeration on the surface and the SEM images revealed a clear evidence for enhancement of morphology in all three samples. 2% PVP-(Mn–CdS) sample showed a good development in morphology when compared with other two samples and the best sample showed formation of nanorods below the surface of nanoparticles. Further, Mn–CdS, 1% PVP-(Mn–CdS) and 2% PVP- (Mn–CdS) was indulged to investigate the cationic degradation. The photocatalytic activities of three samples were carried out with loading different amount of the catalysts and 30 mg catalyst 2% PVP- (Mn–CdS) loaded dye solution showed a considerable degradation of methylene blue dye. The 30 mg catalyst (2% PVP-Mn-CdS) showed 98% efficiency under visible light irradiation for about 2 h. The best candidate, 30 mg catalyst (2% PVP-Mn-CdS) investigated for its reusability. The catalyst showed almost 98% of efficiency up to three cycles which confirmed the level of potential of the sample. 2% PVP-(Mn–CdS) sample would be promising candidate in wastewater treatment. It can be further utilized for removing dyes from wastewater in wastewater remediation process. Highlights: 2% PVP-(Mn–CdS) showed good developmental morphology. 2% PVP-(Mn–CdS) enhanced the cationic degradation. 2% PVP-(Mn–CdS)) showed 98% efficiency under visible light irradiation.